An Evaluation of the Preparatory EFL English Course (Book 6) for Iraqi Islamic Schools from Teachers' Perspective (Eurasian Journal of Research, Development and Innovation, 2022)
The current study aims at Evaluating the Preparatory EFL English Course ( Book 6) for Iraqi Islamic Schools. The sample of the study includes fifty-four teachers (34 boys(63%) and 20 girls(37%) )who are actually teaching English in the selected schools during the academic year 2018-2019 (in the Islamic schools ) in the city of Baghdad and Kirkuk who represent 77% of the total number of teachers' population. A questionnaire has been conducted and applied to the selected sample. The required data are collected and analysed statistically. The study reaches to results such as , ( Book6) does not supply students with the skills of writing and listening at the same time